Pharmacokinetics of Unboosted Atazanavir in Treatment-experienced HIV-infected Children, Adolescents and Young Adults. Issue 12 (December 2016) - Cressey, Tim R.; Hazra, Rohan; Wiznia, Andrew; Foca, Marc; Jean-Philippe, Patrick; Graham, Bobbie; King, Jennifer R.; Britto, Paula; Carey, Vincent J.; Acosta, Edward P.; Yogev, Ram
Abstract : HIV protease inhibitor use in pediatrics is challenging due to the poor palatability and/or toxicity of concomitant low-dose ritonavir. Atazanavir without ritonavir (unboosted) is not recommended for patients with prior virologic failure, a common problem for perinatally-infected adolescents. Atazanavir 400 mg once-daily provided suboptimal exposure. Higher unboosted doses or splitting the daily dose to twice-daily warrants investigation in this treatment-experienced population.